A Gothic Reformation: Tractarianism in the Scottish Episcopal Church. Issue 2 (October 2019) - Harris, Eleanor M.
Abstract : From the mid-eighteenth century Episcopalianism experienced a remarkable resurgence, reflected in membership, church building and – equally – the development of distinctive liturgical and aesthetic traditions. This article explores the influences of Tractarianism, Romanticism and the gothic literature and architecture on the development of a distinctly Scottish Episcopal tradition.